Modelling of surface morphologies in disordered organic semiconductors using fractal methods / Kong Yeo Lee - Kong , Yeo Lee (2017)

(untitled)
Organic semiconductor structures have been studied extensively mainly in attempts to improve charge transfer rate at the organic thin film interfaces. Enhancement on carriers transport and performance, integration of heterostructures and composite materials, and improving life-span of the devices are among the major focuses. Surface morphologies are often investigated to characterize various interface processes including charge transfer and surface contact between layers in thin films. The total effective interface area and root mean square (rms) of surface height fluctuations are among the common parameters that often used to corroborate device performance upon modifying surface properties. In this study, three different but complementary approaches are used to characterize geometrical features of microstructure morphologies in disordered organic nickel tetrasulfonated phthalocyanine (NiTsPc) films, namely the power spectral density analysis, variogram method based on generalized Cauchy process model and grayscale fractal box counting approach. The objectives of this research work are (i) to investigate geometrical features of microstructure morphologies in disordered organics solar cell by using fractal methods, (ii) to relate fractal parameters with carrier transport properties, and (iii) to study and quantify device performance based on microstructure morphological features. It is shown that each of these approaches offers certain perspective about the complex morphologies often found in disordered thin films and thus joint interpretations of these approaches offer better characterizations of the surface properties, filling the gap left by others. The morphologies are also interpreted in the context of percolation network supported by the photocurrent density measurements. Higher electric conductivity is observed for thin films with higher fractal dimension but also enhanced when there exists spatially correlated morphologies in the form of network and this has enhanced charge transport at interfaces.